Prediction of the prognosis of advanced hepatocellular carcinoma by TERT promoter mutations in circulating tumor DNA. Issue 4 (7th September 2020) - Hirai, Mami; Kinugasa, Hideaki; Nouso, Kazuhiro; Yamamoto, Shumpei; Terasawa, Hiroyuki; Onishi, Yuma; Oyama, Atsushi; Adachi, Takuya; Wada, Nozomu; Sakata, Masahiro; Yasunaka, Tetsuya; Onishi, Hideki; et al.
Abstract: Background andAim: Human telomerase reverse transcriptase ( TERT ) promoter mutations were the most prevalent mutations in patients with hepatocellular carcinoma (HCC). We tried to detect the mutations with plasma circulating tumor DNA (ctDNA) in patients with advanced HCC and elucidated their clinical utility. Methods: Circulating tumor DNA in plasma was extracted from 130 patients with advanced HCC who were treated with systemic chemotherapy ( n  = 86) or transcatheter arterial chemoembolization ( n  = 44), and TERT promoter mutations were examined with digital droplet polymerase chain reaction. The correlations between these mutations and the clinical outcome of patients were analyzed. Results: Of the 130 patients examined, 71 patients (54.6%) were positive for TERT promoter mutations in ctDNA, of which 64 patients were −124bp G > A and 10 were −146bp G > A. The presence of TERT promoter mutations was correlated with large intrahepatic tumor size ( P  = 0.05) and high des‐gamma carboxyprothrombin ( P  = 0.005). Overall survival of the patients with the mutations was significantly shorter than those without them ( P  < 0.001), and the patients with high (≥ 1%) fractional abundance of the mutant alleles showed shorter survival than those with low (< 1%) fractional abundance. Multivariate analysis revealed that TERT promoter mutation (hazard ratio [HR]: 1.94; 95% confidence interval [CI], 1.18–3.24; P  < 0.01), systemic chemotherapy (HR: 2.38; 95% CI, 1.29–4.57; P  < 0.01), and vascular invasion (HR: 2.16; 95% CI, 1.22–3.76; P  < 0.01) were significant factors for poor overall survival. Conclusions: TERT promoter mutations in ctDNA were associated with short survival and could be a valuable biomarker for predicting the prognosis of patients with advanced HCC.